2015 IEEE International Conference on Signal and Image Processing Applications (ICSIPA) 2015
DOI: 10.1109/icsipa.2015.7412226
|View full text |Cite
|
Sign up to set email alerts
|

Machining process classification using PCA reduced histogram features and the Support Vector Machine

Abstract: Being able to identify machining processes that produce specific machined surfaces is crucial in modern manufacturing production. Image processing and computer vision technologies have become indispensable tools for automated identification with benefits such as reduction in inspection time and avoidance of human errors due to inconsistency and fatigue. In this paper, the Support Vector Machine (SVM) classifier with various kernels is investigated for the categorization of machined surfaces into the six machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The smooth zone (characterized by less ruggedness) is increased with the rate of feed decrease. In [157], the following outcomes were inferred from the analysis of the results using the ANOVA procedure and the S/N ratio methodology.…”
Section: Surface Characteristics Measurement For Part's Surface Gener...mentioning
confidence: 99%
“…The smooth zone (characterized by less ruggedness) is increased with the rate of feed decrease. In [157], the following outcomes were inferred from the analysis of the results using the ANOVA procedure and the S/N ratio methodology.…”
Section: Surface Characteristics Measurement For Part's Surface Gener...mentioning
confidence: 99%
“…e larger the separating or functional margin, the lower the classification error [46]. Originally, SVMs were designed for binary classification; however, they can also be used for nonlinear classification problems with the help of kernels [47], hence making them more versatile for classification problems [46]. Linear SVM is used since it is simple to implement.…”
Section: Support Vector Machine Support Vector Machinesmentioning
confidence: 99%
“…The results of the experiments showed that the proposed contrast-adjusting methods have performance similar to minimum error thresholding (MET) and are generally better than Otsu's method. In 2015, M. W. Ashour et al [9] proposed the approach of the Support Vector Machine adaptive threshold segmentation are used. And then, the contours from the binary image are extracted.…”
Section: Introductionmentioning
confidence: 99%